2021
DOI: 10.1101/2021.06.20.449148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental plasticity in visual cortex is necessary for normal visuomotor integration and visuomotor skill learning

Abstract: The experience of coupling between motor output and visual feedback is necessary for the development of visuomotor skills and shapes visuomotor integration in visual cortex. Whether these experience-dependent changes involve plasticity in visual cortex remains unclear. Here, we probed the role of NMDA receptor-dependent plasticity in mouse primary visual cortex (V1) during visuomotor development. Using a conditional knockout of NMDA receptors and a photoactivatable inhibitor of CaMKII, we locally perturbed pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…However, we do not expect the learning of PE neurons to be compromised when all inhibitory synapses are plastic. Recently, it has been shown that NMDA receptor–dependent plasticity in early development is crucial for the responses to unpredictable and predictable stimuli in V1 ( 58 ). This suggests that excitatory plasticity plays a pivotal role in the formation of PE neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not expect the learning of PE neurons to be compromised when all inhibitory synapses are plastic. Recently, it has been shown that NMDA receptor–dependent plasticity in early development is crucial for the responses to unpredictable and predictable stimuli in V1 ( 58 ). This suggests that excitatory plasticity plays a pivotal role in the formation of PE neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on the finding that NMDA receptor antagonists induce schizophrenia-like symptoms (Moghaddam and Javitt, 2012), and that disturbances of NMDA and AMPA receptor related gene expression are associated with schizophrenia (Harrison and Weinberger, 2005; Singh et al, 2020). In V1, it has been shown that NMDA receptors are necessary during visual development to establish normal prediction error signaling (Widmer and Keller, 2021). Thus, it is conceivable that a disruption of glutamatergic signaling in cortex that alters the way internal representations are activated by prediction errors is central to the etiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…All details of data acquisition were described previously (Attinger et al, 2017; Widmer and Keller, 2021). Data are publicly available on https://data.fmi.ch/PublicationSupplementRepo/.…”
Section: Methodsmentioning
confidence: 99%
“…All details of data acquisition were described previously (Attinger et al, 2017;Widmer and Keller, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation